2021
DOI: 10.1101/2021.07.31.454200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene regulatory networks controlling temporal patterning, neurogenesis, and cell fate specification in the mammalian retina

Abstract: Gene regulatory networks (GRNs), consisting of transcription factors and their target cis-regulatory sequences, control neurogenesis and cell fate specification in the developing central nervous system, but their organization is poorly characterized. In this study, we performed integrated scRNA-seq and scATAC-seq analysis from both mouse and human retina to profile dynamic changes in gene expression, chromatin accessibility and transcription factor footprinting during retinal neurogenesis. We identified multip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 110 publications
2
19
0
Order By: Relevance
“…Constructs tested included a GFAP-mCherry control and a range of different transcription factors that have been previously reported to reprogram Müller glia or were candidates for doing so based on their role in regulating neurogenesis and/or retinal neuron specification (Fig. 1A) (Mears et al, 2001; Sharma et al, 2019; Puls et al, 2020; Lyu et al, 2021; Todd et al, 2021; Xiao et al, 2021). To genetically label Müller glia prior to AAV infection, we conducted 3 consecutive intraperitoneal injections of 4-hydroxytamoxifen (4-OHT) from P21-P23 in GlastCreER;Sun1-GFP mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructs tested included a GFAP-mCherry control and a range of different transcription factors that have been previously reported to reprogram Müller glia or were candidates for doing so based on their role in regulating neurogenesis and/or retinal neuron specification (Fig. 1A) (Mears et al, 2001; Sharma et al, 2019; Puls et al, 2020; Lyu et al, 2021; Todd et al, 2021; Xiao et al, 2021). To genetically label Müller glia prior to AAV infection, we conducted 3 consecutive intraperitoneal injections of 4-hydroxytamoxifen (4-OHT) from P21-P23 in GlastCreER;Sun1-GFP mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3), or the bipolar/photoreceptor cell-specific marker Otx2 (Fig. 4) (Lyu et al, 2021). All other constructs tested – including GFAP-Neurod1-mCherry, GFAP-Mybl1-mCherry, GFAP-Insm1-mCherry, GFAP-Atoh7-Ascl1-mCherry, and GFAP-Atoh7-Brn3b-mCherry – showed little mCherry expression in Sun1-GFP-positive Müller glia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, formation of the superficial and deep, but not intermediate, plexus layers requires the activity of the hypoxic response pathway (via the von Hippel-Lindau factor (Vhl) found in amacrine and horizontal cells (Usui et al, 2015). In a recent study that used single cell PCR to generate a genetic regulatory network in the mouse retina, Tbx3 was found in amacrine and Müller glia (Lyu et al, 2021). Overexpression of TBX3 in retinal progenitors at P0 led to an increase of amacrine, retinal ganglion cells, Müller glia, and bipolar cells, but repressed formation of rod photoreceptors (Lyu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that used single cell PCR to generate a genetic regulatory network in the mouse retina, Tbx3 was found in amacrine and Müller glia (Lyu et al, 2021). Overexpression of TBX3 in retinal progenitors at P0 led to an increase of amacrine, retinal ganglion cells, Müller glia, and bipolar cells, but repressed formation of rod photoreceptors (Lyu et al, 2021). Therefore, in future studies, we will determine the effect of Tbx3 loss on all types of retinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that IReNA can be used to integrate scRNA-seq and ATAC-seq to reconstruct gene regulatory networks controlling retinal regeneration and retinal development [7,14]. Through network analysis using IReNA, we identified modular gene regulatory networks and key transcription factors regulating different cell states in retinal Müller glia in zebrafish and mice.…”
Section: Discussionmentioning
confidence: 99%